Regional increase of cerebral cortex thickness in juvenile myoclonic epilepsy. Issue 9 (14th August 2013) - Alhusaini, Saud; Ronan, Lisa; Scanlon, Cathy; Whelan, Christopher D.; Doherty, Colin P.; Delanty, Norman; Fitzsimons, Mary
Summary The goal of this study was to characterize cerebral cortex thickness patterns in juvenile myoclonic epilepsy (JME). Surface‐based morphometry (SBM) was applied to process brain magnetic resonance images acquired from 24 patients with JME and 40 healthy controls and quantify cerebral cortex thickness. Differences in cortical thickness between patients and controls were determined using generalized linear model (covariates: age and gender). In patients with JME, thickness increase was detected bilaterally within localized regions in the orbitofrontal and mesial frontal cortices. Such thickness patterns coexisted with significant bilateral reduction in thalamic volume. These findings confirm that the underlying mechanisms in JME are related to aberrant corticothalamic structure and indicate that frontal cortex abnormalities are possibly linked to regional increase in cerebral cortical thickness.